System design for turbidity control in aquaponic ponds - Aditya Aprilianto; Weny Indah Kusumawati; Harianto; Heri Pratikno (LPPMPK- Universitas Muhammadiyah Cileungsi, 2025)
Aquaculture is fish farming, and hydroponics is the cultivation of plants/vegetables without soil, which means utilizing water and growing media. Aquaponic systems are a combination of fish farming (aquaculture) and soil-less plant/vegetable farming (hydroponics), creating a mutually beneficial relationship. This research aims to design and implement an automated system capable of monitoring and controlling the water turbidity level in aquaponic ponds using the SEN0189 sensor integrated with the Internet of Things (IoT) platform. The developed system utilizes a turbidity sensor, float switch, NodeMCU ESP8266 microcontroller, and connection to the Firebase cloud to enable real-time remote monitoring. The control logic in the system is designed to be able to take automatic water draining and filling actions based on the detected turbidity level parameters. Tests were conducted 98 times, showing a sensor success rate of 92% with 8% non-conforming readings due to program logic mismatches. The tests also revealed the significant influence of environmental lighting, where sensor results at night showed higher values despite clear water conditions. In addition, the system successfully avoided overlapping processes between draining and filling, with an operational success rate of 100% in the overall device test. The results show that the system is effective and reliable for maintaining water quality in aquaponic systems, as well as providing users with the convenience of remotely monitoring and managing water conditions through an IoT connection. This system can be an efficient alternative solution to support the success of fish and plant farming in household and commercial scale aquaponics.